The Charismatic Revolutionary Leadership Trajectories of Fidel Castro and Lázaro Cárdenas: From Guerrillas to Heads of State in the Age of US Imperialism - Joseph J. Garcia (Journal of Global Initiatives, 2020)
After attempting to overthrow the government of Fulgencio Batista in 1953, Fidel Castro fled to Mexico where he, his brother, Raul Castro, Ernesto Che Guevara, and other revolutionaries were later jailed by the Mexican government under the orders of the Batista dictatorship to be returned to Cuba. Using his knowledge of the Mexican Revolution, Castro wrote a letter asking for help from former president and revolutionary general, Lázaro Cárdenas, appealing to his sense of revolutionary history and social justice. Cárdenas was impressed by this young revolutionary and worked to obtain political asylum for he and his comrades. This allowed Castro to enter Texas clandestinely in order to collect funds for the Cuban Revolution. This chance encounter of two revolutionaries is not well known in the annals of Mexico and Cuba, yet provides us with an important historical interaction between two dynamic and charismatic leaders who were uniquely loved by their respective publics, and often clashed with attempted international interventions. Moreover, their relationship did not end with the release of Castro in 1956 as they continued to influence each other. Yet, historians have largely ignored the connection between Castro and Cárdenas. I argue that both men were effective revolutionary leaders who followed similar trajectories as they became highly revered for their charismatic leadership based on their combat experience, victory over national and international challenges, leadership of their nations, and the nationalization of petroleum which institutionalized both revolutions.